Modelo de gestión sostenible para el desarrollo de emprendimientos turísticos en comunidades de la Costa Norte de Manabí - Loor Marcillo, Gladys Maite (2020)
This descriptive-exploratory research with a mixed approach, aims to design a sustainable management model for ventures in communities on the north coast of Manabí; five specific objectives were established: it begins with the tourist diagnosis in the field of community management, which was based on a description of the territory, the identification of community initiatives, their problems and limitations, the use of techniques and tools such as: visits to the field, the community characterization sheet, observation sheet, surveys, multivariate statistical analyzes, interviews with main actors, which made it possible to determine the potentiality and viability of the undertakings, and to carry out a study of demand to determine the client's profile. The second objective established the evaluation of tourism ventures from a business point of view through a checklist of sustainability indicators, a community participation matrix was also designed to measure the degree of intervention in tourism activity, consequently it was determined a list of benefits and damages generated by the community tourist activity. The third objective allowed the identification of elements, processes, activities, strategies and tools relevant to the entrepreneurial subsystem of community tourism at the national level through bibliographic-documentary search. Subsequently, a selection and validation of indicators was carried out to form a sustainable management model, which were validated using the method of expert judgment. Finally, a tourism management model based on community management is proposed considering the particular reality of the northern coast of Manabí, which was validated by expert criteria.